Changing trends in the use of kratom (Mitragyna speciosa) in Southeast Asia. (24th May 2017) - Singh, Darshan; Narayanan, Suresh; Vicknasingam, Balasingam; Corazza, Ornella; Santacroce, Rita; Roman‐Urrestarazu, Andres
Abstract: Objective: Kratom ( Mitragyna speciosa . Korth) is an indigenous medicinal plant of Southeast Asia. This review paper aims to describe the trends of kratom use in Southeast Asia. Design: A literature review search was conducted through ScienceDirect, Scopus, ProMed and Google Scholar. Twenty‐five articles illustrating kratom use in humans in Southeast Asia were reviewed. Results: Kratom has long been used by rural populations in Southeast Asia as a remedy for common ailments, to fight fatigue from hard manual work, as a drink during social interaction among men, and in village religious functions. Studies based on self‐reports suggest that prolonged kratom use does not result in serious health risks or impair social functioning. Two recent trends have also emerged: (a) Kratom is reportedly being used to ease withdrawal from opioid dependence in rural settings; whereas (b) in urban areas, adulterated kratom cocktails are being consumed by younger people to induce euphoria. Conclusions: Legal sanctions appear to have preceded serious scientific investigations into the claimed benefits of ketum. More objective‐controlled trials and experiments on humans need to be conducted to validate self‐report claims by kratom users in the community.